The legal framework for freedom of expression in the visual and audio media in the Kingdom of Saudi Arabia - Ahmed Abdulrahman Al-Babtain; Kazim Mounis Aziz (International Journal of Law Research and Studies, 2026)
This study aimed to analyze and evaluate the legal framework governing the audiovisual media sector in the Kingdom of Saudi Arabia, and to examine its role in regulating freedom of expression amidst the rapid changes brought about by digital openness and the objectives of the Kingdom’s Vision 2030. The study sought to answer the fundamental question of the adequacy of current legislation in achieving a delicate balance between protecting national identity and religious values ​​on the one hand, and keeping pace with the demands of media openness and technological development on the other. The study adopted a descriptive-analytical approach to examine legal texts and regulations (such as the Audiovisual Media Law and the Anti-Cybercrime Law), in addition to using a comparative approach to assess the compatibility of these laws with international standards. The study population consisted of media organizations and related institutions, while the sample comprised three main categories: (media professionals, legal and regulatory professionals, and a sample of the Saudi public) whose opinions were gathered through questionnaires and interviews. This study is significant due to the scarcity of research that has specifically addressed the modern legal framework governing audiovisual media in the Kingdom. Its findings aim to provide a critical perspective that contributes to the development of media policies and bridges the legislative gap that may arise from the rapid pace of digital media, thereby ensuring responsible media practices that support national development.